A baseline scenario of municipal solid waste management. (30th April 2020) - Bowan, Patrick Aaniamenga; Kayaga, Sam; Fisher, Julie
The baseline scenarios of municipal solid waste management (MSWM) activities that will expose the specific challenges militating against sustainable waste management in many developing countries are not properly documented or not understood. This paper established a baseline scenario of municipal solid waste management (MSWM) in Ghana, through material flow analysis and understanding of MSW handling practices, using the Wa Municipality as a case study. The study was theoretically based on empirical observation and an exploratory design. The findings showed that sustainable waste management has remained elusive because MSWM in the case study area and Ghana in general, consist of some waste collection, transportation and open dumping, where the entire amount of waste is open dumped without pretreatment. The sorting of waste at the generation sources, and the provision of adequate MSWM infrastructure, through an integrated solid waste management system can ensure sustainable waste management in the country.